The Effect of Financial Ratios on Profit-Sharing Financing in Bank Syariah Indonesia Post Merger - Deta Trinalti Oktavia (Journal of Innovative and Creativity, 2025)
The purpose of this study is to analyze the effect of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO) on profit-sharing financing. The object of this research is Bank Syariah Indonesia, which is the result of a merger between Bank Syariah Mandiri, BNI Syariah, and BRI Syariah. The research data were obtained from the quarterly published financial reports of Bank Syariah Indonesia for the period 2021–2025. Data analysis was conducted using the EViews application. The results show that Non-Performing Financing (NPF) and Operating Expenses to Operating Income (BOPO) have a negative relationship with profit-sharing financing, while the Financing to Deposit Ratio (FDR) has a positive effect on profit-sharing financing. The independent variables, consisting of NPF, FDR, and BOPO, simultaneously have a significant effect on the dependent variable, profit-sharing financing. These findings are consistent with the theory of Islamic banking intermediation, which emphasizes that the stability of internal financial performance is a key factor influencing a bank’s ability to distribute profit-sharing-based financing to its customers.